PEMBERIAN SANKSI TERHADAP TINDAK PIDANA MEMBELI DAN MENYALAHGUNAKAN NARKOTIKA GOLONGAN I BUKAN TANAMAN: Giving Sanctions Against the Crime of Buying and Misusing Narcotics Group I Non-Plants - Furqon, Mohamad Insan; Iskandar, Anang (AMICUS CURIAE, 2024)
Sanctions for the crime of narcotics abuse for oneself are mostly carried out by imposing prison sentences as in case number 287/Pid.Sus/2021/PN.Dgl which is subject to criminal sanctions for 2 years. The issues raised are 1) Is the imposition of sanctions against the perpetrators of the crime of buying and abusing Narcotics Group I non-plants in accordance with Article 127 of the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics? 2. What is the reason for the Judge not imposing a Rehabilitation Sanction? The method in this study uses a normative legal research type with an analytical descriptive research type. The data used are secondary data obtained through literature studies and then analyzed qualitatively, drawing conclusions using deductive logic. The results of the study showed that the sentence given by the panel of judges to the defendant was inappropriate because it violated the purpose of the Narcotics Law, namely to guarantee arrangements for medical rehabilitation and social rehabilitation for narcotics abusers and addicts as stated in Article 4 letter d Law Number 35 of 2009 , then the judge who decides the case does not pay attention to the provisions referred to in Articles 54, 55 and Article 103. The judge's consideration in imposing a prison sentence solely so that the defendant gets a deterrent effect is contrary to the purpose of the Narcotics Law, namely guaranteeing rehabilitation efforts for abusers and addicts narcotics.